2012
DOI: 10.1021/jp211670g
|View full text |Cite
|
Sign up to set email alerts
|

Water Barrier Properties in Biaxially Drawn Poly(lactic acid) Films

Abstract: Crystallization is among the easiest ways to improve polymer barrier properties because of the tortuosity increase within the material and the strong coupling between amorphous and crystalline phases. In this work, poly(lactic acid) (PLA) films have undergone α' thermal crystallization or different drawing processes. Although no effect of α' thermal crystallization on water permeability is observed, the drawing processes lead to an enhancement of the PLA barrier properties. This work clearly shows that, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 67 publications
12
87
1
Order By: Relevance
“…In some cases, constancy or even an increase in the oxygen permeability with an increasing crystallinity degree of PLA was found [6,9]. A similar result was also observed in the case of the water vapour permeability of crystallized PLA [10,11]. Kanehashi et al [12] did an impressive review on approximately 300 studies concerning the relationship between gas permeability and crystallinity of various polymers.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In some cases, constancy or even an increase in the oxygen permeability with an increasing crystallinity degree of PLA was found [6,9]. A similar result was also observed in the case of the water vapour permeability of crystallized PLA [10,11]. Kanehashi et al [12] did an impressive review on approximately 300 studies concerning the relationship between gas permeability and crystallinity of various polymers.…”
Section: Introductionmentioning
confidence: 66%
“…The content of RAF in polylactide, X RA , depends on the conditions of crystallization and can vary from 0% to 35% [30]. Although this approach may look simplistic since it limits the description of the amorphous phase to its structure without considering its dynamics, the studies of Guinault et al [14], Drieskens et al [13], and Delpouve et al [11] proposed that an important amount of RAF is prejudicial for the barrier properties of PLA. The content of the RAF can be calculated after…”
Section: Structural Description Of the Amorphous Phase And Its Coopermentioning
confidence: 99%
“…The presence of this relatively stiff phase has an impact on material properties. For example, some previous studies showed that the rigid amorphous phase resulted especially in an increase of the elastic modulus [36e38] and had a strong influence on the barrier properties [39,40].…”
Section: Characterization Of the Amorphous Phase During Crystallizationmentioning
confidence: 99%
“…11 The average interchain distance in the mesomorphic form is substantially reduced with regard to the most probable spacing of the amorphous chains. 10 The weight fraction of each phase has been calculated from the intensity profiles 6 and from the average heat flow curves (shown in a previous paper 21 ) obtained by means of TMDSC. Both techniques lead to similar results; TMDSC results are presented in Table 1.…”
Section: Microstructural Characterizationmentioning
confidence: 99%